1990
DOI: 10.1093/ajcn/52.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal responses to the stresses of lactation concurrent with pregnancy and of short recuperative intervals

Abstract: In many regions of the world, women breastfeed one child while pregnant with the next. Among rural Guatemalan women participating in a nutrition-supplementation trial, lactation overlapped with pregnancy in 253 of 504 (50.2%) of the pregnancies. For cases where overlap occurred, 41.4% continued to breast-feed into the second trimester and 3.2%, in the third trimester. The maternal and fetal responses to the energetic stresses of overlap and of the duration of the recuperative (nonpregnant, nonlactating) interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…Merchant et al 7,8 reported that an overlap was associated with a nonsignificant decrease of 57 g in birth weight; the effect increased with the overlap duration. Studies with the appropriate design to look at birth outcomes (risk of low birth weight or prematurity) have not been conducted yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Merchant et al 7,8 reported that an overlap was associated with a nonsignificant decrease of 57 g in birth weight; the effect increased with the overlap duration. Studies with the appropriate design to look at birth outcomes (risk of low birth weight or prematurity) have not been conducted yet.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Despite this, the practice is common. 7,8,28,29 In Bangladesh, an estimated 20% of women who were lactating and pregnant were still lactating at the beginning of the ninth month. 28 In Guatemala, 50% of pregnant women were breastfeeding an older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cases where overlap occurred, 41.4% continued to breast-feed into the second trimester and 3.2%, in the third trimester. The energetic stresses of overlap did not significantly affect fetal growth [7]. With increasing firsthand experience among health professionals; many wellrespected sources are asserting that even breast feeding is safe in healthy pregnancies [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gestation and lactation have significant costs in terms of macro-and micronutrients, limiting their availability for maternal immune processes (Lunn, 1994;Prentice, 1994;Prentice and Prentice, 1988). In particular, progressive deterioration of maternal nutritional status from the cumulative demands of reproduction can lead to "maternal depletion," particularly when interbirth intervals are short and/or available nutritional resources are low (Merchant and Martorell, 1988;Merchant et al, 1990;Wood, 1994). Although the direct impact on immune function has not been considered, it can be assumed that low energy reserves impair maternal immunocompetence in these situations.…”
Section: Adulthoodmentioning
confidence: 99%